ANALISIS PEMBELAJARAN KONSEP DASAR IPS TERHADAP KEBUDAYAAN PALEMBANG PADA HASIL BELAJAR MAHASISWA PGSD UNIVERSITAS PGRI PALEMBANG (PENELITIAN KUALITATIF-DESKRIPTIF MAHASISWA PGSD UNIVERSITAS PGRI PALEMBANG SEMESTER 2 TAHUN 2017/2018) - Manullang, Febriani Rotua (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2018)
ABSTRACTThis study aims to describe the difficulties of PGSD students in student learning outcomes through qualitative-descriptive methods using data triangulation, namely documentation, interviews, and observation. In testing the ability of mathematical understanding, researchers used multiple choice test questions that were first tested for their level of validity and reliability. Then the results were obtained that only 15 of the 30 questions that could be used in the learning outcomes test of the basic social science concepts of PGSD students. In this study, students were divided into 3 levels of ability categories, namely high, medium, and low. The results obtained are questions that are categorized as"difficult" 15 students who can answer, while the questions that are categorized as "medium" students can already understand and answer the purpose of the problem and students can find out the basic concepts such as the history of the culture of the city of Palembang. The researcher interviewed and gave a little training on the culture of the city of Palembang, so that students could answer the questions given. The conclusion obtained is that 27% of students have high abilities, 43% of students have moderate abilities, and 27% of students have low abilities. The training of local cultural questions to students will help them in recognizing Palembang's cultural history.Keywords : Basic concept of IPS, Palembang Culture, learning outcomes